Analysing Cancer Care Informatics Through The Lens of The United Nations Sustainable Development Goals - A Review and Assessment - Brooks, Ian; Longhurst, James; Kossmann, Mario; Mansour, Asem; Odeh, Mohammed; Tbakhi, Abdelghani (2018 1st International Conference on Cancer Care Informatics (CCI), 2018)
Cancer Care Informatics (CCI) and its impacts are assessed using the United Nations Sustainable Development Goals (SDGs). The positive and negative impacts of CCI on the SDGs are considered through a literature review and expert assessment. There has not been a prior publication of such an assessment and this could contribute to more holistic governance of CCI. The paper reviews the individual SDGs along with consideration of the 17 SDGs as a whole. Whilst the relationship of CCI with the achievement of SDG3 (Good Health and Well-Being) is the obvious impact, CCI also has impacts on other underpinning targets or indicators within the SDG framework. For example, the Greenhouse Gas emissions from the electricity consumed by CCI computer systems will have a negative effect on SDG13 Climate Change. Using the SDG lens helps us to identify the other direct and indirect impacts of CCI on Sustainable Development and affords the opportunity to manage deliberately such impacts as improving equality of access, elimination of modern slavery and delivering CCI education.